Construction and Characterization of Hexon-Chimeric Adenoviruses: Specification of Adenovirus Serotype - Gall, Jason G. D. (American Society for Microbiology, 1998)
This study has used the strategy of gene replacement to characterize the contribution of the adenovirus (Ad) capsid protein hexon to serotype definition. By replacing the Ad type 5 (Ad5) hexon gene with sequences from Ad2, we have changed the type specificity of the chimeric virus. The type-determining epitopes are primarily associated with loop 1 of hexon and, to a much lesser degree, with loop 2. In spite of the serotype distinctiveness of the chimeric hexon viruses, epitope similarity between the vectors resulted in a low level of cross-reactive neutralizing antibody, which in combination with activated cellular and innate arms of the immune system is sufficient to suppress gene transduction following readministration in vivo.